Perancangan Daya Tarik Wisata untuk Pengembangan Desa Wisata dan Inovasi Nilam di Desa Ranto Sabon Kabupaten Aceh Jaya - Erwan, Friesca; Lufika, Raihan Dara; Dewi, Cut; Muhammad, Syaifullah; Muslim, Muslim; Ilyas, Suhrawardi (JURNAL MASTER PARIWISATA; Volume 09, Nomor 01, Juli 2022DO - 10.24843/JUMPA.2022.v09.i01.p04, 2022)
Desa Ranto Sabon is a marginal area in Aceh Jaya District, Aceh Province. The village owns natural resources which can be developed into tourist attractions to encourage the development of Innovation and Tourism Village. Designing the tourism attractions are carried out using three methods, to cover Penta Helix collaboration, designing a roadmap, and conducting a technical workshop. The Penta Helix collaboration involves stakeholders from the government, universities, industry and business, the community, and the media. The roles of each parties are identified in detail to obtain significant involvement in designing the tourist attractions. Furthermore, this activity prepares a roadmap as a guide for the stakeholders in carrying out activities and achieving the goals. Lastly, this activity conducted a technical workshop to perform tourism mindset transformation and improve the knowledge and skills of the community. Designing a tourism attraction in Desa Ranto Sabon produces three tourism concepts which are ecotourism, agrotourism and patchouli-based education tourism (edu-tourism). Keywords: designing tourist attractions; ecotourism; agrotourism; patchouli edu-tourism.